Meeting the challenge: between depopulation and new industrialization : innovations in VET in Eastern Germany - Barabasch, Antje [Verfasser] (My University, 2012)
"Despite the heavy investments in the economic development of East German industry, the region still faces immanent structural challenges that affect the provision of vocational education and training (VET), in particular apprenticeships, and the availability of a well skilled workforce. In this article the situation of the economy as well as new trends in the provision of VET in the Eastern states are outlined in order to provide necessary background information for the understanding of various innovative approaches that are taken to meet current and future workforce development needs. Although some of these approaches are viewed critically by industry stakeholders, politicians and researchers, the examination of selected projects indicates that they can be viewed as innovative attempts leading to positive change. Despite the fact that some of these projects are intended to implement sustainable structures, the results of the interviews point to the need for further public financial support." (Authors' abstract, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; G 1.1.1 Demografie; I 2 Regionen; S 4.1 Finanzierungsquellen; I 1 Internationale Berufsbildung; I 2.1.1 Neue Bundesländer; Berufsbildungssystem; Berufsbildungspolitik; Innovation; Jugendlicher; Abwanderung; Bevölkerungsrückgang; Demografischer Wandel; Strukturschwacher Raum; Berufsbildendes Schulwesen; Betriebliche Berufsausbildung; Ausbildungsbereitschaft; Ausbildungsförderung; Internationale Zusammenarbeit; Best practice; Ostdeutschland